Các yếu tố ảnh hưởng đến năng lực dạy học bằng tiếng Anh của sinh viên sư phạm trong bối cảnh triển khai định hướng đưa tiếng Anh trở thành ngôn ngữ thứ hai trong trường học: Nghiên cứu tại Trường Đại học Thủ đô Hà Nội - Vũ Thị Thúy (Tạp chí Giáo dục, 2026)
The policy orientation of promoting English as a second language in schools and gradually developing a teaching workforce capable of delivering instruction through English has created pressing demands for teacher education institutions. In this context, enhancing pre-service teachers’ competence in English-medium instruction is considered a critical strategy for the effective implementation of Vietnam’s Project on English as a second language in schools for the period 2025-2035, with a vision to 2045. The study employed a quantitative research design. Data were collected through a questionnaire survey administered to 1,136 pre-service teachers at Hanoi Metropolitan University. Participants were selected using convenience sampling. The findings identified five key factors affecting pre-service teachers’ English-medium instruction competence: English language competence, pedagogical and professional competence, content and language integration competence (CLIL), the teacher education environment, and students’ motivation and professional awareness. Among these factors, motivation and professional awareness emerged as the strongest predictor of English-medium instruction competence. Based on the identified factors and their respective levels of influence, the study proposes several recommendations for enhancing English-medium instruction competence among pre-service teachers, thereby contributing to educational innovation and international integration in the context of ongoing educational reform.